Borderless Heat Hazards With Bordered Impacts. Issue 9 (12th September 2021) - Brimicombe, Chloe; Di Napoli, Claudia; Cornforth, Rosalind; Pappenberger, Florian; Petty, Celia; Cloke, Hannah L.
Abstract: Heatwaves are increasing in frequency, duration, and intensity due to climate change. They are associated with high mortality rates and cross‐sectional impacts including a reduction in crop yield and power outages. Here we demonstrate that there are large deficiencies in reporting of heatwave impacts in international disasters databases, international organization reports, and climate bulletins. We characterize the distribution of heat stress across the world focusing on August in the Northern Hemisphere, when notably heatwaves have taken place (i.e., 2003, 2010, and 2020) for the last 20 years using the ERA5‐HEAT reanalysis of the Universal Thermal Comfort Index and establish heat stress has grown larger in extent, more so during a heatwave. Comparison of heat stress against the emergency events impacts database and climate reports reveals underreporting of heatwave‐related impacts. This work suggests an internationally agreed protocol should be put in place for impact reporting by organizations and national government, facilitating implementation of preparedness measures, and early warning systems. Plain Language Summary: Heat extremes are increasing in frequency, duration, and intensity due to climate change. Their impacts include a rise in death rates, a decrease in how much of a crop is produced and power outages. Here we show that there is a lack of reporting of impacts in international organization reports, international disaster databases. Further, heat stress, an impact of heat extremes is characterized using an index that is human‐centric. With a focus on August and the Northern Hemisphere, we show that heat stress has grown in extent and is presenting a growing risk to more of the population over this millennium. This work suggests that organizations and national governments should come together to agree a protocol for how to best report heat impacts, so that we can be better prepared for them. Key Points: In the Northern Hemisphere, heat stress during the month of August is growing in area and is larger during a heatwave Heat stress area increase is greater over the populated land surface than the total land surface during August Impacts of Heatwaves are not sufficiency captured by international meteorological organization reports and emergency events impacts database